The Return of the Peasant : Land Reform in Post-Communist Romania. - Cartwright, A. L. (Routledge Revivals, 2017)
"This title was first published in 2001. Of the many far reaching issues facing post-communist states in the wake of the collapse of communist rule, few have continued to pose such dilemmas for future progress as the land question. This book provides a historical account of national and local attempts to reform land ownership and agricultural production and in particular, the way in which land law defined the land question. Using archive work to demonstrate the selectivity of the law in righting wrongs and case studies to illustrate the practical obstacles to attempts at reconstructing the pre-communist system, this work is a critical and detailed portrait of the forces that stand to shape the future of post-communist rural life."--Provided by publisher.